Data mining applications with R - Zhao, Yangchang, 1977-; Cen, Yonghua (Elsevier, AP, 2014)
"Data Mining Applications with R is a great resource for researchers and professionals to understand the wide use of R, a free software environment for statistical computing and graphics, in solving different problems in industry. R is widely used in leveraging data mining techniques across many different industries, including government, finance, insurance, medicine, scientific research and more. This book presents 15 different real-world case studies illustrating various techniques in rapidly growing areas. It is an ideal companion for data mining researchers in academia and industry looking for ways to turn this versatile software into a powerful analytic tool. R code, Data and color figures for the book are provided at the RDataMining.com website. Helps data miners to learn to use R in their specific area of work and see how R can apply in different industries. Presents various case studies in real-world applications, which will help readers to apply the techniques in their work. Provides code examples and sample data for readers to easily learn the techniques by running the code by themselves."--Resumé vydavatele
Keywords: dolování dat; R (software); data mining; případové studie; elektronické knihy; case studies; electronic books